Household Labor and Gender Roles in the Age of Smart Homes: A Systematic Literature Review - Sidik, Sangputri; Retnosari, Putri; Hidayati, Niswatin Nurul; Sangaji, Ayu Indira (DISCOURSE: Indonesian Journal of Social Studies and Education, 2025)
In recent years, smart home devices have been promoted as tools for enhancing efficiency and convenience in household management. However, their influence on domestic labor and gender roles remains underexplored, particularly regarding their impact on the lives of female domestic workers. This systematic review examines the impact of smart home technologies on domestic workers and the implications for gender roles. This study employs a comprehensive search strategy across Scopus databases to select relevant articles, ensuring a thorough examination of existing literature on the intersection of smart home technology, domestic labor, and gender. The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines help researchers plan and carry out systematic reviews systematically, maintain transparency, reduce bias, and achieve rigor in review processes. The results point out that potential smart home technologies can both empower and constrain domestic workers. On the one hand, these technologies can enhance workers' autonomy by reducing the physical demands of domestic tasks. On the other hand, they can increase surveillance and control over domestic workers, potentially intensifying their workload and reinforcing traditional gender norms. The integration of smart home technologies into domestic settings has complex implications for gender equity. While these technologies offer opportunities to challenge traditional gender roles, they can also reinforce existing inequalities if not carefully implemented.